Plant phenology: a critical controller of soil resource acquisition - Nord, Eric A; Lynch, Jonathan P (Journal of experimental botany, 2009)
Plant phenology, the timing of plant growth and development, is changing in response to global climate change. Changing temperature, soil moisture, nitrogen availability, light, and elevated CO2 are all likely to affect plant phenology. Alteration of plant phenology by global climate change may alter the ability of plants to acquire soil resources (water and nutrients) by altering the timing and duration of the deployment of roots and leaves, which drive resource acquisition. The potential importance of phenologically-driven changes in soil resource acquisition for plant fitness and productivity have received little attention. General hypotheses are proposed for how plant acquisition of soil resources may be affected by the alteration of phenology. It is expected that the acquisition of mobile resources will be approximately proportional to total transpiration. Alteration of phenology that increases total transpiration should increase, while changes in phenology that reduce transpiration should decrease the acquisition of mobile resources. The acquisition of immobile resources will be approximately proportional to root length duration, thus changes in phenology that increase growth duration should increase the acquisition of immobile resources and vice versa. For both groups of resources, longer growing seasons would tend to increase resource acquisition, and shorter growing seasons would tend to decrease resource acquisition. In the case of resources that exhibit seasonal variability in availability, the synchrony of resource availability and acquisition capacity is important, and subject to disturbance by the alteration of phenology.